Pendekatan Studi Islam: Sejarah Awal Perkenalan Islam dengan Tasawuf - Miftahul Ulum (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2020)
Sufism is the most important religious heritage for Muslims who can bring it closer to the God. Therefore, Sufism and Islam cannot be separated. Although initially there was a debate about the origins of Sufism which many orientalists say came from outside Islam. However, then some Orientalists reviewed their opinions, one of which was R.A. Nicholson finally referred to Sufism to Islamic sources. And Rasullah is both a source and a prime example for Sufis based on the Qur'an and its Sunnah. In its development Sufism consists of four periods, namely: the period of the Prophet, Friends, Tabi'in and the spread of Sufism. The main points of the teachings are focused on moral Sufism, practice, and philosophy.